Genetic-environment interaction and genetic advance of superior wheat mutants by Francis and Kannenberg’s method (Progressive Agriculture, 2019)
Increasing salinity, in the coastal area, is one of the major reasons of reducing wheat production. It is necessary to develop high yielding salt tolerant genotypes for sustainable yield of wheat in these areas. In our previous study, 37 lines were selected based on Francis and Kannenberg (1978) method following mean and standard deviation (SD) constructed in scattered plot diagram. In the present study, these selected lines along with ‘Prodip’ were grown in two different conditions: one is non-saline condition (BINA, Mymensingh) and another is saline condition (BINA, Satkhira). These wheat genotypes were evaluated to select the best performing lines which are stable in both the environment for their yield attributes. In RCBD trail with 3 replications, it was revealed that there were variations for plant height, flag leaf duration, spike length, spikelets per spike, 100-grain weight, number of tiller and yield per plant. Plant height, spikelets per spike and yield per plant showed higher heritability, higher phenotypic coefficient of variation and genetic advance. However, spike length, number of tiller and flag leaf duration showed medium heritability. Genotype-environment interaction and stability analysis showed variation for plant height, flag leaf duration, 100 grain weight and yield per plant and the line L-61-18, L-879-2, L-879-22, L-880-7, L-880-18 and L-880-43 were the most potential and stable genotypes in both saline and non-saline environments for yield. Higher selection score was obtained from L-880-38 followed by L-879-34 and L-880-36 and lower selection score was obtained from L-880-34 respectively. Importance should be given on plant height, spike length, spikelet per spike and yield per plant for selection of salt tolerant wheat line in future wheat research programme.Progressive Agriculture 30 (1): 20-31, 2019